Enrobing Ceremony for Municipal Court Judge R. L. "Chip" Putnam in Jury Assembly Room - Watkins, Howard::::::::: (1987)
Supervisor Bruce Bronzan speaking at lectern; Seated: Judges Steven Vartabedian and Stephen Henry